Luta camponesa pela terra no latifúndio da Araupel: um estudo do histórico dominial, práticas de grilagem e vidas camponesas - Hammel , Ana Cristina (2020)
The thesis has as thematic the agrarian question that involves the struggle for agrarian reform in the properties of Pinhal Ralo and Rio das Cobras, located in the Central-Southern mesoregion of Parana, which formed the Araupel latifundium. The text approaches how, historically, social capitalist relations of production have molded the occupancy, property and use of the land and the resistance of the peasants as one of the determinants of the production of sociability that involved the movement of a sea of land (a continuous latifundium of 114 thousand hectares of land) and a sea of people (more than 5 thousand families) that disputed for land. The study of peasant lives in the Laranjeiras countryside, locus where the Pinhal Ralo and Rio das Cobras properties are located, led us to the study of illegal occupation, until then occupied by squatters, caboclos and indigenous people. The research paths took us to various sources of ages, which in addition to expressing the daily life of peasants in these areas, took it to evidence of practices of ilegal occupation, expropriation and violence against the local population. The lawsuits filed in the District of Laranjeiras do Sul between the years 1950 and 1960 denounce the practices of squatting and the expulsion of peasants, supported and carried out by agents and agencies of the state of Parana. These sources constituted an important documentation to understand the illegal occupation occurred in the region, the overlapping of land between the properties, Fazenda Laranjeiras, Colônia Adelaide, Colônia Fortuna, Erva Mate, Andradas and Rio das Cobras. These elements raised in period sources brought the need to understand the transition from the public domain to the private domain of the lands that constituted the Araupel latifundium, which concentrated more than 100 thousand hectares of land in the 1940s. The domain history, refers to the concentration of the land by São Paulo businessmen José Ermírio de Moraes and Paulo Pereira Ignácio in the 1940s, which resulted in a series of vices at the origin that remain in disputes today (2020) at the Regional Court of the 4th region (TRF-4). In the 1970s, these lands were resold to three groups of businessmen from Rio Grande do Sul, formed by the Giacomet, Marodin and Maisonnave families, who founded the company Madeireira Giacomet Marodin. The control of this latifundium by Giacomt Marodin / Araupel aggravated the conflict, as the company's control practices and the exploitation of wood generated new forms of expropriation and expulsion of peasants with the advance on land occupied by squatters. In this local environment the situation was aggravated with the construction of hydroelectric plants on the Iguaçu River in the 1970s. In this context, there was also agrarian conflict and the peasants' struggle for land for work, housing and freedom. The struggle for land gave rise to camps and settlement projects. As conquests of agrarian reform, four settlements were created - Ireno Alves dos Santos, 1997, Marcos Freire, 1998, Celso Furtado and Dez de Maio, in 2005 - and four camps - Herdeiros da Terra of 1º de Maio (2014); Dom Tomás Balduino (2015), Vilmar Bordin and Leonir Orbak, (2016) - in both properties. This fraction of the conquered territory represented a victory for the peasants, organized by the Landless Movement, and also in a business reconfiguration of the Araupel latifundium, through the use of public money obtained with the expropriation of more than 50 thousand hectares of land. In the areas conquered for agrarian reform, new forms of use and life on land and peasant recreation itself (agroecological production, Rural Education and Landless Youth) were also created, and experiences of non-capitalist work and resistance within capitalism.